Indo-Pakistan Trade Through Wagah Border: Situation Analysis and Future Prospects - Syed , Sumair Ahmed (Journal of Pakistan Administration, 2024)
This research paper aims to study the trade dynamics of Pakistan and India, including an analysis of past and present trade patterns, the identification of obstacles and challenges, the exploration of prospective growth prospects, and the evaluation of potential returns and risks of expanded trade. Research methodology includes a review of current literature on the topic, comparison with international best practices, analysis of data and reports from government sources with relevant statistics, surveys and focus group interviews with traders on past commercial activity and reforms needed in the case of Wagah-Attari route revitalization. Historic tensions between Pakistan and India, particularly over the Kashmir issue, have hampered geo-economic cooperation between the two neighbors. India’s unilateral abrogation of Article 370 on August 5th, 2019, led to a complete trade ban through the Wagah-Attari border. Since the start of trade, the trade balance has remained negative for Pakistan, and Pakistan has imported goods worth Rs. 313,181 million and exported items of only Rs. 115,493 million to India through Wagah, Pakistan. Moreover, the government has collected overall a substantial amount of revenue, Rs. 16,096.3 million, through the imposition of taxes and import duty. Furthermore, Pakistan imported mainly Cotton Yarn and Plastic Granules in 2018-19 from India. Key export items were minerals, salt, dry dates, and cement. The Wagah-Attari route was also used for the Afghan Transit trade. The Afghan trade transported goods with having total worth is Rs. 173,394 million. The potential of India-Pakistan border trade through Wagah is huge. Both markets have comparative advantages that may bring mutual benefits. Given India’s rise as a major economic and trading heavyweight, Pakistan stands to gain from economic relationships. The resumption of trade at Wagah will be beneficial in spurring the sluggish growth of economic activity and exchange in Pakistan. In previous years, the trade gap between the two neighbors was in India’s favor. The SAFTA framework can serve as a guide in restarting trade on beneficial terms that may improve overall economic integration of the South Asia region. An analysis of international best practices also examines trade between countries that are not on the best of political terms. Specific recommendations, such as diplomatic negotiations, infrastructure upgradation, business reforms, visa and customs law changes, utilizing SAFTA, eroding trade barriers, bilateral banking agreements, and rationalizing tariffs, have been detailed in order to ensure smooth trade renewal and maximize dividends for both sides.